Relationship between food insecurity and diabetes among patients in Saudi Arabia - Hanbazaza, Mahitab; Alzahrani, Sami; Makki, Ghada; Almihmadi, Ghalia; Mohammed, Nawahil (Progress in Nutrition, 2022)
Background: Food insecurity (FI) is a major determinant of nutritional status, which could influence the self-care practices of diabetic patients. Objective: To assess the prevalence of FI and examine the relationship between FI and self-management practices among patients with diabetes. Methods: A cross-sectional survey was conducted on 229 patients at the diabetes clinic in King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Results: The prevalence of FI was 26.2%, and it was more prevalent among non-Saudis, unemployed participants, and those with low household incomes (